Antistatic and antibacterial fiber and preparation method thereof
The method of polymerizing the double bond-containing polyester, grafting with 4-propyleneoxy-2-hydroxybenzophenone, and combining with porous organic polymer to coat silica nanoparticles, anti-static antibacterial fibers are prepared, which solves the problems of polyester fibers being flammable in high-temperature environments, lack of antibacterial properties, lack of sufficient UV protection and easy accumulation of static electricity, and achieves the improvement of multiple properties of the fibers.
Patent Information
- Application Number
- CN202411639400.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-18
AI Technical Summary
Existing polyester fibers are flammable in high temperature environments, lack antibacterial properties, do not have sufficient UV protection, and are prone to accumulation of static electricity.
The double bond-containing polyester is formed by polymerizing terephthalic acid, sodium isophthalic acid-5-sulfonate and 1,4-butene glycol and grafting with 4-propyleneoxy-2-hydroxybenzophenone to form a modified polyester. Then, silica nanoparticles, 1,2-bis(4-pyridyl)ethylene and tris(4-chlorophenyl)phosphine were reacted to obtain porous organic polymer-coated silica nanoparticles. Finally, the modified polyester and porous organic polymer-coated silica nanoparticles were mixed and melt-spinned to prepare antistatic antibacterial fibers.
The fiber has excellent antistatic properties, flame retardancy, antibacterial properties and UV resistance, which significantly improves the safety and durability of the fiber in high temperature environments.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fibers, in particular to an antistatic and antibacterial fiber and a preparation method thereof. Background Art
[0002] Polyester fiber is a kind of polymer compound formed by polycondensation of organic dibasic acid and diol. Its main characteristics are good elasticity and shape stability, wrinkle resistance and wear resistance. Although polyester fiber has attracted much attention due to its excellent mechanical properties, durability and wide range of applications, it still has some shortcomings.
[0003] Existing polyester fibers generally face the problem of flammability, which limits their application in high-temperature environments or fields with high fire safety requirements. In addition, traditional polyester fibers also lack effective antibacterial properties, which limits their use in medical and health applications that require sanitary conditions; at the same time, in application fields such as outdoor products, existing polyester fibers generally do not provide sufficient anti-ultraviolet protection, resulting in the fibers being prone to aging and performance degradation after long-term exposure to sunlight; in addition, due to the non-conductive nature of polyester, these fibers are also prone to accumulate static electricity, which not only brings inconvenience in wearing and use, but also may pose a safety hazard in flammable environments. Therefore, although polyester fibers perform well in many aspects, their limitations in flame retardancy, antibacterial, anti-ultraviolet and antistatic properties still need to be overcome through technological innovation. The antistatic and antibacterial fiber prepared by the present invention has excellent antistatic, flame retardant, antibacterial and anti-ultraviolet properties. Summary of the invention
[0004] The purpose of the present invention is to provide an antistatic and antibacterial fiber and a preparation method thereof to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] The invention discloses an antistatic antibacterial fiber. The antistatic antibacterial fiber is prepared by polymerizing terephthalic acid, 5-sodium sulfonate of isophthalic acid and 1,4-butene glycol to generate a double-bond polyester, grafting the double-bond polyester and 4-propyleneoxy-2-hydroxybenzophenone to obtain a modified polyester; reacting silica nanoparticles, 1,2-di(4-pyridyl)ethylene and tri(4-chlorophenyl)phosphine to obtain porous organic polymer-coated silica nanoparticles; and mixing the modified polyester and the porous organic polymer-coated silica nanoparticles and performing melt spinning to obtain the antistatic antibacterial fiber.
[0007] A method for preparing an antistatic and antibacterial fiber comprises the following preparation steps:
[0008] (1) Under nitrogen protection, weigh terephthalic acid, sodium 5-sulfoisophthalate, 1,4-butene glycol and antimony trioxide and mix them evenly, heat to 160-170°C for reaction for 40-50 minutes, then heat to 230-240°C, stir for reaction for 2-2.5 hours, and stir at a speed of 200-300 r / min. After the reaction, reduce the pressure at a pressure reduction rate of 0.4-0.5 kPa / min and increase the temperature at a heating rate of 1-2°C / min. After the temperature reaches 270-280°C and the pressure is less than 0.1 kPa, dry in a vacuum drying oven at 70°C for 6-8 hours, and the vacuum degree of the vacuum drying oven is 0.08 MPa to obtain a polyester containing double bonds;
[0009] (2) Mixing the double bond-containing polyester, 4-propyleneoxy-2-hydroxybenzophenone and diisopropylbenzene peroxide uniformly, adding the mixture into a torque rheometer mixer for kneading, wherein the kneading temperature is 270-280° C., the kneading time is 8-10 min, and the kneading speed is 50-60 r / min to obtain a modified polyester;
[0010] (3) Weigh 12-14 parts by mass of silica nanoparticles, 0.01-0.015 parts of cuprous iodide, 0.3-0.5 parts of tetrakis(triphenylphosphine)palladium(0), 50-60 parts of a triethylamine toluene mixture, 0.6-0.8 parts of 1,2-di(4-pyridyl)ethylene, and 1-2 parts of tri(4-chlorophenyl)phosphine, and add the silica nanoparticles, cuprous iodide, and tetrakis(triphenylphosphine)palladium(0) to the triethylamine toluene mixture in sequence. Repeat ultrasonication three times, each time for 15 minutes, with an ultrasonic power of 20-40kHz, continue to add 1,2-di(4-pyridyl)ethylene and tri(4-chlorophenyl)phosphine, raise the temperature to 80-90°C under a nitrogen atmosphere, stir and react for 18-20 hours, with a stirring speed of 300-400r / min, filter and wash with methanol for 3-5 times, and dry at 50-60°C for 6-8 hours to obtain porous organic polymer-coated silica nanoparticles;
[0011] (4) The modified polyester and porous organic polymer-coated silica nanoparticles are uniformly mixed in a mass ratio of 100:3-5, the mixture is heated to 130-140°C and dried for 48-50 hours, and then the mixture is sent to a twin-screw high-speed composite spinning machine for spinning to obtain primary fibers. The primary fibers are stretched on a parallel stretching machine to obtain antistatic and antibacterial fibers.
[0012] As an optimization, the molar ratio of terephthalic acid, 5-sodium sulfoisophthalate, 1,4-butene diol and in step (1) is 1:0.2-0.3:1.3-1.5, and the mass of antimony trioxide is 0.03-0.05 times that of terephthalic acid.
[0013] As an optimization, the mass ratio of the double bond-containing polyester, 4-propyleneoxy-2-hydroxybenzophenone and diisopropylbenzene peroxide in step (2) is 50-60:1:0.03-0.05.
[0014] As an optimization, the silica nanoparticles in step (3) have a particle size of 300 nm and are purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. The triethylamine-toluene mixed solution consists of triethylamine and toluene, wherein the volume ratio of triethylamine to toluene is 1:1.
[0015] As an optimization, the spinning process parameters of the twin-screw high-speed composite spinning machine in step (4) are as follows: the spinneret specification is 0.3mm*36f, the spinneret hole aspect ratio is 1:2, the spinning speed is 700m / min, the spinning temperature is 270°C, and the drawing process conditions are as follows: hot roller temperature is 65°C, setting temperature is 150°C, drawing speed is 300m / min, and drawing multiple is 3.2.
[0016] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0017] When preparing the antistatic antibacterial fiber, the present invention comprises the following steps: polymerizing terephthalic acid, 5-sodium sulfoisophthalic acid and 1,4-butene glycol to generate a double-bond polyester, grafting the double-bond polyester and 4-propyleneoxy-2-hydroxybenzophenone to obtain a modified polyester; reacting silica nanoparticles, 1,2-di(4-pyridyl)ethylene and tri(4-chlorophenyl)phosphine to obtain porous organic polymer-coated silica nanoparticles; and mixing the modified polyester and the porous organic polymer-coated silica nanoparticles and performing melt spinning to obtain the antistatic antibacterial fiber.
[0018] Firstly, terephthalic acid, 5-sodium sulfoisophthalic acid and 1,4-butenediol are polymerized to generate a polyester containing a double bond, and the polyester containing a double bond and 4-propyleneoxy-2-hydroxybenzophenone are grafted to obtain a modified polyester; terephthalic acid, 5-sodium sulfoisophthalic acid and 1,4-butenediol are subjected to a condensation reaction of a dibasic acid and a diol to obtain a polyester containing a hydrophilic sulfonic acid group and a double bond in the main chain, and the double bonds on the main chain and 4-propyleneoxy-2-hydroxybenzophenone undergo a free radical reaction through melt grafting, and a hydroxybenzophenone structure is grafted on the main chain, and the keto group and the hydroxyl group in the structure can generate an intramolecular hydrogen bond to form a chelate ring, which, after absorbing ultraviolet light energy, undergoes thermal vibration of the molecule, destroys the internal hydrogen bond, opens the chelate ring, and converts the energy of the ultraviolet light into heat energy and releases it, thereby giving the fiber anti-ultraviolet properties.
[0019] Secondly, silica nanoparticles, 1,2-di(4-pyridyl)ethylene and tri(4-chlorophenyl)phosphine are reacted to obtain porous organic polymer-coated silica nanoparticles; 1,2-di(4-pyridyl)ethylene and tri(4-chlorophenyl)phosphine undergo nucleophilic substitution reaction to obtain quaternary ammonium salt-type conjugated porous polymer, and the silica nanoparticles are wrapped during the polymerization process; the quaternary ammonium salt cation can interact with the negative charge on the bacterial cell membrane, causing the cell membrane to rupture, thereby killing the bacteria. Since the quaternary ammonium salt structure is stably embedded in the porous polymer skeleton, it can exhibit long-lasting antibacterial properties and give the fiber antibacterial properties. The conjugated system in the polymer allows π electrons to move freely within the molecule, thereby promoting the mobility of electrons and enhancing the conductivity of the fiber. At the same time, the phosphorus element in the polymer structure can also give the fiber certain flame retardant properties. Due to the excellent stability of silica, the polymer-coated silica nanoparticles can not only further improve the flame retardant properties of the fiber, but also enhance the fiber's high heat resistance and tensile strength and other properties.
[0020] Finally, the modified polyester and porous organic polymer-coated silica nanoparticles are reacted and melt-spun to obtain antistatic and antibacterial fibers. The negatively charged sulfonic acid groups on the modified polyester can undergo electrostatic adsorption with the positively charged porous organic polymer-coated silica nanoparticles, which can enhance the bonding force between the two materials and the dispersibility of the silica nanoparticles, thereby improving the mechanical properties of the fiber. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] The silica nanoparticles used in the following examples and comparative examples have a particle size of 300 nm and were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Example 1
[0023] A method for preparing an antistatic antibacterial fiber, the method comprising the following preparation steps:
[0024] (1) Weigh terephthalic acid, sodium 5-sulfoisophthalic acid and 1,4-butene glycol in a molar ratio of 1:0.2:1.3, and then weigh antimony trioxide in an amount 0.03 times the mass of terephthalic acid. Under nitrogen protection, mix terephthalic acid, sodium 5-sulfoisophthalic acid, 1,4-butene glycol and antimony trioxide evenly, heat to 170°C for reaction for 50 min, then heat to 240°C, stir for reaction for 2.5 h, and stir at a speed of 300 r / min. After the reaction is completed, reduce the pressure at a pressure reduction rate of 0.5 kPa / min and increase the temperature at a heating rate of 2°C / min. After the temperature reaches 280°C and the pressure is 0.1 kPa, dry in a vacuum drying oven at 70°C for 8 h, and the vacuum degree of the vacuum drying oven is 0.08 MPa to obtain a polyester containing double bonds;
[0025] (2) The double bond-containing polyester, 4-propyleneoxy-2-hydroxybenzophenone and diisopropylbenzene peroxide were uniformly mixed in a molar ratio of 50:1:0.03, and added into a torque rheometer mixer for mixing, wherein the mixing temperature was 280° C., the mixing time was 10 min, and the mixing speed was 60 r / min to obtain a modified polyester;
[0026] (3) Triethylamine and toluene were mixed in a volume ratio of 1:1 to prepare a triethylamine toluene mixed solution, and 12 parts of silica nanoparticles, 0.01 parts of cuprous iodide, 0.3 parts of tetrakis(triphenylphosphine)palladium(0), 50 parts of triethylamine toluene mixed solution, 0.6 parts of 1,2-di(4-pyridyl)ethylene, and 1 part of tri(4-chlorophenyl)phosphine were weighed in mass proportions. The silica nanoparticles, cuprous iodide and tetrakis(triphenylphosphine)palladium(0) were added to the triethylamine toluene mixed solution in sequence and ultrasonicated three times for 15 min each time at an ultrasonic power of 40 kHz. 1,2-di(4-pyridyl)ethylene and tri(4-chlorophenyl)phosphine were added continuously. The temperature was raised to 90°C under a nitrogen atmosphere, and the reaction was stirred for 20 h at a stirring speed of 400 r / min. The mixture was filtered and washed with methanol for 5 times, and dried at 60°C for 8 h to obtain porous organic polymer-coated silica nanoparticles.
[0027] (4) The modified polyester and the porous organic polymer-coated silica nanoparticles were mixed uniformly in a mass ratio of 100:3, heated to 140°C and dried for 50 hours, and then fed into a twin-screw high-speed composite spinning machine for spinning to obtain nascent fibers, which were then stretched on a parallel stretching machine, wherein the spinning process parameters of the spinning machine were: spinneret specification 0.3 mm*36f, spinneret hole aspect ratio 1:2, spinning speed 700 m / min, spinning temperature 270°C, stretching process conditions: hot roller temperature 65°C, setting temperature 150°C, stretching speed 300 m / min, and stretching multiple 3.2. Antistatic and antibacterial fibers were obtained. Example 2
[0028] A method for preparing an antistatic antibacterial fiber, the method comprising the following preparation steps:
[0029] (1) Weigh terephthalic acid, sodium 5-sulfoisophthalic acid and 1,4-butene glycol in a molar ratio of 1:0.25:1.4, and then weigh 0.04 times the mass of antimony trioxide of terephthalic acid. Under nitrogen protection, mix terephthalic acid, sodium 5-sulfoisophthalic acid, 1,4-butene glycol and antimony trioxide evenly, heat to 165°C for reaction for 45 minutes, then heat to 235°C, stir for reaction for 2.3 hours, and stir at a speed of 250 r / min. After the reaction is completed, reduce the pressure at a pressure reduction rate of 0.45 kPa / min and increase the temperature at a heating rate of 1.5°C / min. After the temperature reaches 275°C and the pressure is 0.08 kPa, dry in a vacuum drying oven at 70°C for 7 hours, and the vacuum degree of the vacuum drying oven is 0.08 MPa to obtain a polyester containing double bonds;
[0030] (2) The double bond-containing polyester, 4-propyleneoxy-2-hydroxybenzophenone and diisopropylbenzene peroxide were uniformly mixed in a molar ratio of 55:1:0.02, and added into a torque rheometer mixer for mixing, wherein the mixing temperature was 275° C., the mixing time was 9 min, and the mixing speed was 55 r / min to obtain a modified polyester;
[0031] (3) Triethylamine and toluene were mixed in a volume ratio of 1:1 to prepare a triethylamine toluene mixed solution, and 13 parts of silica nanoparticles, 0.012 parts of cuprous iodide, 0.4 parts of tetrakis(triphenylphosphine)palladium(0), 55 parts of triethylamine toluene mixed solution, 0.7 parts of 1,2-di(4-pyridyl)ethylene, and 1 part of tri(4-chlorophenyl)phosphine were weighed in parts by mass. The silica nanoparticles, cuprous iodide and tetrakis(triphenylphosphine)palladium(0) were added to the triethylamine toluene mixed solution in sequence and ultrasonicated three times for 15 min each time at an ultrasonic power of 30 kHz. 1,2-di(4-pyridyl)ethylene and tri(4-chlorophenyl)phosphine were added continuously. The temperature was raised to 85°C under a nitrogen atmosphere, and the reaction was stirred for 19 h at a stirring speed of 350 r / min. The mixture was filtered and washed with methanol for 4 times, and dried at 55°C for 7 h to obtain porous organic polymer-coated silica nanoparticles.
[0032] (4) The modified polyester and the porous organic polymer-coated silica nanoparticles were mixed uniformly in a mass ratio of 100:4, heated to 135°C and dried for 49 hours, and then fed into a twin-screw high-speed composite spinning machine for spinning to obtain nascent fibers, which were then stretched on a parallel stretching machine, wherein the spinning process parameters of the spinning machine were: spinneret specification 0.3 mm*36f, spinneret hole aspect ratio 1:2, spinning speed 700 m / min, spinning temperature 270°C, stretching process conditions: hot roller temperature 65°C, setting temperature 150°C, stretching speed 300 m / min, and stretching multiple 3.2. Antistatic and antibacterial fibers were obtained. Example 3
[0033] A method for preparing an antistatic antibacterial fiber, the method comprising the following preparation steps:
[0034] (1) Weigh terephthalic acid, sodium 5-sulfoisophthalic acid and 1,4-butene glycol in a molar ratio of 1:0.3:1.5, and then weigh 0.05 times the mass of antimony trioxide of terephthalic acid. Under nitrogen protection, mix terephthalic acid, sodium 5-sulfoisophthalic acid, 1,4-butene glycol and antimony trioxide evenly, heat to 160°C for reaction for 40 minutes, then heat to 230°C, stir for reaction for 2 hours, and stir at a speed of 200-300 r / min. After the reaction is completed, reduce the pressure at a pressure reduction rate of 0.4 kPa / min and increase the temperature at a heating rate of 1°C / min. After the temperature reaches 270°C and the pressure is 0.07 kPa, dry in a vacuum drying oven at 70°C for 6 hours, and the vacuum degree of the vacuum drying oven is 0.08 MPa to obtain a polyester containing double bonds;
[0035] (2) The double bond-containing polyester, 4-propyleneoxy-2-hydroxybenzophenone and diisopropylbenzene peroxide were uniformly mixed in a molar ratio of 60:1:0.05, and added into a torque rheometer mixer for mixing, wherein the mixing temperature was 270° C., the mixing time was 8 min, and the mixing speed was 50 r / min to obtain a modified polyester;
[0036] (3) Triethylamine and toluene were mixed in a volume ratio of 1:1 to prepare a triethylamine toluene mixed solution, and 14 parts of silica nanoparticles, 0.015 parts of cuprous iodide, 0.5 parts of tetrakis(triphenylphosphine)palladium(0), 60 parts of triethylamine toluene mixed solution, 0.8 parts of 1,2-di(4-pyridyl)ethylene, and 2 parts of tri(4-chlorophenyl)phosphine were weighed in mass proportions. The silica nanoparticles, cuprous iodide and tetrakis(triphenylphosphine)palladium(0) were added to the triethylamine toluene mixed solution in sequence and ultrasonicated three times for 15 min each time at an ultrasonic power of 20 kHz. 1,2-di(4-pyridyl)ethylene and tri(4-chlorophenyl)phosphine were added continuously. The temperature was raised to 80°C under a nitrogen atmosphere, and the reaction was stirred for 18 h at a stirring speed of 300 r / min. The mixture was filtered and washed with methanol three times, and dried at 50°C for 6 h to obtain porous organic polymer-coated silica nanoparticles.
[0037] (4) The modified polyester and porous organic polymer-coated silica nanoparticles were mixed evenly in a mass ratio of 100:5, heated to 140°C and dried for 48 hours, and then sent to a twin-screw high-speed composite spinning machine for spinning to obtain nascent fibers. The nascent fibers were stretched on a parallel stretching machine, wherein the spinning process parameters of the spinning machine were as follows: spinneret specification was 0.3 mm*36 f, spinneret hole aspect ratio was 1:2, spinning speed was 700 m / min, spinning temperature was 270°C, stretching process conditions were as follows: hot roller temperature was 65°C, setting temperature was 150°C, stretching speed was 300 m / min, and stretching multiple was 3.2, thereby obtaining antistatic and antibacterial fibers.
[0038] Comparative Example 1
[0039] The preparation method of the antistatic antibacterial fiber of Comparative Example 1 is different from that of Example 2 in that step (2) is not included, and step (4) is modified as follows: the double-bond polyester and the porous organic polymer-coated silica nanoparticles are mixed uniformly at a mass ratio of 100:4, the temperature is raised to 135°C and dried for 49 hours, and the fibers are fed into a twin-screw high-speed composite spinning machine for spinning to obtain nascent fibers, and the nascent fibers are stretched on a parallel stretching machine, wherein the spinning process parameters of the spinning machine are: the spinneret specification is 0.3mm*36f, the spinneret hole aspect ratio is 1:2, the spinning speed is 700m / min, the spinning temperature is 270°C, and the stretching process conditions are: the hot roller temperature is 65°C, the setting temperature is 150°C, the stretching speed is 300m / min, and the stretching multiple is 3.2. The antistatic antibacterial fiber is obtained.
[0040] Comparative Example 2
[0041] The preparation method of the antistatic antibacterial fiber of Comparative Example 2 is different from that of Example 2 in that step (3) is modified to prepare a triethylamine toluene mixed solution by mixing triethylamine and toluene in a volume ratio of 1:1, weighing 0.012 parts of cuprous iodide, 0.4 parts of tetrakis(triphenylphosphine)palladium(0), 55 parts of triethylamine toluene mixed solution, 0.7 parts of 1,2-di(4-pyridyl)ethylene, and 1 part of tri(4-chlorophenyl)phosphine in parts by mass, adding cuprous iodide and tetrakis(triphenylphosphine)palladium(0) to the triethylamine toluene mixed solution in sequence and repeating ultrasonication three times, each time for 15 minutes, with an ultrasonic power of 30 kHz, continuing to add 1,2-di(4-pyridyl)ethylene and tri(4-chlorophenyl)phosphine, heating to 85°C under a nitrogen atmosphere, reacting for 19 hours, filtering with suction and washing with methanol for 4 times, and drying at 55°C for 7 hours to obtain a porous organic polymer;
[0042] Step (4) is modified as follows: the modified polyester and the porous organic polymer are uniformly mixed in a mass ratio of 100:4, the temperature is raised to 135°C and dried for 49 hours, and the mixture is fed into a twin-screw high-speed composite spinning machine for spinning to obtain nascent fibers, and the nascent fibers are stretched on a parallel stretching machine, wherein the spinning process parameters of the spinning machine are: spinneret specification is 0.3 mm*36f, spinneret hole aspect ratio is 1:2, spinning speed is 700 m / min, spinning temperature is 270°C, and stretching process conditions are: hot roller temperature is 65°C, setting temperature is 150°C, stretching speed is 300 m / min, and stretching multiple is 3.2, thereby obtaining antistatic and antibacterial fibers.
[0043] Comparative Example 3
[0044] The preparation method of the antistatic antibacterial fiber of Comparative Example 3 is different from that of Example 2 in that step (3) is not included, and step (4) is modified as follows: the modified polyester and the silica nanoparticles are uniformly mixed in a mass ratio of 100:4, the temperature is raised to 135°C and dried for 49 hours, and the mixture is fed into a twin-screw high-speed composite spinning machine for spinning to obtain nascent fibers, and the nascent fibers are stretched on a parallel stretching machine, wherein the spinning process parameters of the spinning machine are: the spinneret specification is 0.3 mm*36f, the spinneret hole aspect ratio is 1:2, the spinning speed is 700 m / min, the spinning temperature is 270°C, and the stretching process conditions are: the hot roller temperature is 65°C, the setting temperature is 150°C, the stretching speed is 300 m / min, and the stretching multiple is 3.2, thereby obtaining the antistatic antibacterial fiber.
[0045] Flame retardant performance test
[0046] Test method: The antistatic and antibacterial fibers prepared in all comparative examples and embodiments were tested using an Italian ATS-FAAR high temperature oxygen index tester in accordance with CB / T 2406-1993 "Plastic Combustion Performance Test Method Oxygen Index Method". The results are shown in Table 1.
[0047] Table 1
[0048]
[0049] From the comparison of the experimental data of Examples 1-3 and Comparative Examples 1-3 in Table 1, it can be found that the antistatic and antibacterial fiber prepared in the present invention has good flame retardant properties.
[0050] By comparison, the limiting oxygen index of Examples 1-3 is greater than that of Comparative Examples 2 and 3, indicating that silica nanoparticles, 1,2-di(4-pyridyl)ethylene and tri(4-chlorophenyl)phosphine are reacted to obtain porous organic polymer-coated silica nanoparticles; 1,2-di(4-pyridyl)ethylene and tri(4-chlorophenyl)phosphine undergo nucleophilic substitution reaction to obtain quaternary ammonium salt-type conjugated porous polymer, and the silica nanoparticles are encapsulated during the polymerization process; the phosphorus element in the polymer structure can give the fiber certain flame retardant properties, and the polymer-encapsulated silica nanoparticles can further improve the flame retardant properties of the fiber due to the excellent stability of silica.
[0051] Test Example 2
[0052] Mechanical properties testing
[0053] Test method: The mechanical properties of the antistatic and antibacterial fibers prepared in all embodiments and comparative examples were tested using an XQ-2 fiber strength and elongation tester. The fiber clamping distance was 20 mm, the stretching rate was 20 mm / min, the test temperature was room temperature, and each group of fibers was tested 30 times to take the average value. The results are shown in Table 2.
[0054] UV resistance test
[0055] Test method: All antistatic and antibacterial fibers prepared in the examples and comparative examples were laid flat on a sample rack, and the sample rack was placed in a UV light box parallel to the UV lamp tube, with a radiation intensity of 1100 W / m 2 The temperature in the box was 60°C, the humidity was 60%, the fiber was 10 cm away from the lamp, and the irradiation time was 60 hours. After the irradiation, the breaking strength was tested according to the test method of mechanical properties test and the breaking strength retention rate was calculated. The results are shown in Table 2.
[0056] Table 2
[0057]
[0058] From the comparison of the experimental data of Examples 1-3 and Comparative Examples 1-3 in Table 2, it can be found that the antistatic and antibacterial fiber prepared in the present invention has good mechanical properties and anti-ultraviolet properties.
[0059] By comparison, the breaking strength of Examples 1-3 is greater than that of Comparative Example 2, and the breaking strength retention rate of Examples 1-3 after ultraviolet irradiation is greater than that of Comparative Example 1, indicating that silica nanoparticles, 1,2-di(4-pyridyl)ethylene and tri(4-chlorophenyl)phosphine are reacted to obtain porous organic polymer-coated silica nanoparticles; 1,2-di(4-pyridyl)ethylene and tri(4-chlorophenyl)phosphine undergo nucleophilic substitution reaction to obtain quaternary ammonium salt-type conjugated porous polymer, and the silica nanoparticles are encapsulated during the polymerization process; the polymer-encapsulated silica nanoparticles can enhance the mechanical properties of the fiber due to the excellent stability of silica. Terephthalic acid, 5-sodium sulfoisophthalic acid and 1,4-butenediol are polymerized to generate a polyester containing a double bond, and the polyester containing a double bond and 4-propyleneoxy-2-hydroxybenzophenone are grafted to obtain a modified polyester; terephthalic acid, 5-sodium sulfoisophthalic acid and 1,4-butenediol are subjected to a condensation reaction of a dibasic acid and a diol to obtain a polyester containing a hydrophilic sulfonic acid group and a double bond in the main chain, and the double bonds on the main chain and 4-propyleneoxy-2-hydroxybenzophenone undergo a free radical reaction through melt grafting, and a hydroxybenzophenone structure is grafted on the main chain, and the keto group and the hydroxyl group in the structure can generate an intramolecular hydrogen bond to form a chelate ring, which, after absorbing ultraviolet light energy, undergoes thermal vibration of the molecule, destroys the internal hydrogen bond, opens the chelate ring, and converts the energy of the ultraviolet light into heat energy and releases it, thereby giving the fiber anti-ultraviolet properties.
[0060] Test Example 3
[0061] Antibacterial performance test
[0062] Test method: According to the oscillation method in GB / T20944.3-2008 "Evaluation of antibacterial properties of textiles", the antibacterial properties of the super-hydrophobic flame-retardant fibers prepared in the examples and comparative examples were tested. The results are shown in Table 3.
[0063] Table 3
[0064]
[0065] From the comparison of the experimental data of Examples 1-3 and Comparative Examples 1-3 in Table 3, it can be found that the antistatic and antibacterial fiber prepared in the present invention has good antibacterial properties.
[0066] By comparison, the antibacterial rate of Examples 1-3 is greater than that of Comparative Example 3, indicating that the silica nanoparticles, 1,2-di(4-pyridyl)ethylene and tri(4-chlorophenyl)phosphine are reacted to obtain porous organic polymer-coated silica nanoparticles; 1,2-di(4-pyridyl)ethylene and tri(4-chlorophenyl)phosphine undergo nucleophilic substitution reaction to obtain quaternary ammonium salt-type conjugated porous polymer, and the silica nanoparticles are wrapped during the polymerization process; the quaternary ammonium salt cations can interact with the negative charges on the bacterial cell membrane, causing the cell membrane to rupture, thereby killing the bacteria and giving the fiber antibacterial properties.
[0067] Test Example 4
[0068] Antistatic performance test
[0069] Test method: According to GB / T14342-1993 "Test method for specific resistance of synthetic staple fibers", the antistatic and antibacterial fibers prepared in all embodiments and comparative examples were tested. All embodiments and comparative examples were placed at 20°C and 65% relative humidity for 4 hours, and then the specific resistance was tested using a YG321 specific resistance meter from Changzhou Textile Instrument Factory. The results are shown in Table 4.
[0070] Table 4
[0071]
[0072] From the comparison of the experimental data of Examples 1-3 and Comparative Examples 1-3 in Table 4, it can be found that the antistatic and antibacterial fiber prepared in the present invention has good antistatic properties.
[0073] By comparison, the mass specific resistance of Examples 1-3 is smaller than that of Comparative Example 3, indicating that silica nanoparticles, 1,2-di(4-pyridyl)ethylene and tri(4-chlorophenyl)phosphine are reacted to obtain porous organic polymer-coated silica nanoparticles; 1,2-di(4-pyridyl)ethylene and tri(4-chlorophenyl)phosphine undergo nucleophilic substitution reaction to obtain quaternary ammonium salt-type conjugated porous polymer, and the silica nanoparticles are encapsulated during the polymerization process; the conjugated system in the polymer allows π electrons to move freely within the molecule, thereby promoting the mobility of electrons and enhancing the conductivity of the fiber.
[0074] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. An antistatic and antibacterial fiber, characterized in that: The antistatic antibacterial fiber is prepared by polymerizing terephthalic acid, 5-sodium sulfonate of isophthalic acid and 1,4-butene glycol to generate a double-bond polyester, grafting the double-bond polyester and 4-propyleneoxy-2-hydroxybenzophenone to obtain a modified polyester; reacting silica nanoparticles, 1,2-di(4-pyridyl)ethylene and tri(4-chlorophenyl)phosphine to obtain porous organic polymer-coated silica nanoparticles; and mixing the modified polyester and the porous organic polymer-coated silica nanoparticles and performing melt spinning to obtain the antistatic antibacterial fiber.
2. A method for preparing an antistatic and antibacterial fiber, characterized in that: The method comprises the following preparation steps: (1) Under nitrogen protection, weigh terephthalic acid, sodium 5-sulfoisophthalic acid, 1,4-butenediol and antimony trioxide and mix them evenly. The molar ratio of terephthalic acid, sodium 5-sulfoisophthalic acid, 1,4-butenediol and is 1:0.2-0.3:1.3-1.5, and the mass of antimony trioxide is 0.03-0.05 times that of terephthalic acid; heat to 160-170℃ for reaction for 40-50min, and then heat to 23 0-240°C, stirring reaction for 2-2.5h, stirring speed of 200-300r / min, after the reaction is completed, reducing the pressure at a pressure reduction rate of 0.4-0.5kPa / min and heating at a heating rate of 1-2°C / min, after the temperature reaches 270-280°C and the pressure is less than 0.1kPa, drying in a vacuum drying oven at 70°C for 6-8h, the vacuum degree of the vacuum drying oven is 0.08MPa, to obtain a polyester containing double bonds; (2) Mixing the double bond-containing polyester, 4-propyleneoxy-2-hydroxybenzophenone and diisopropylbenzene peroxide in a mass ratio of 50-60:1:0.03-0.05, adding the mixture into a torque rheometer mixer for kneading at a temperature of 270-280° C., a mixing time of 8-10 min, and a mixing speed of 50-60 r / min to obtain a modified polyester; (3) Weigh 12-14 parts by mass of silica nanoparticles, 0.01-0.015 parts of cuprous iodide, 0.3-0.5 parts of tetrakis(triphenylphosphine)palladium(0), 50-60 parts of a triethylamine toluene mixture, 0.6-0.8 parts of 1,2-di(4-pyridyl)ethylene, and 1-2 parts of tri(4-chlorophenyl)phosphine, and add the silica nanoparticles, cuprous iodide, and tetrakis(triphenylphosphine)palladium(0) to the triethylamine toluene mixture in sequence. Repeat ultrasonication three times, each time for 15 minutes, with an ultrasonic power of 20-40kHz, continue to add 1,2-di(4-pyridyl)ethylene and tri(4-chlorophenyl)phosphine, raise the temperature to 80-90°C under a nitrogen atmosphere, stir and react for 18-20 hours, with a stirring speed of 300-400r / min, filter and wash with methanol for 3-5 times, and dry at 50-60°C for 6-8 hours to obtain porous organic polymer-coated silica nanoparticles; (4) The modified polyester and porous organic polymer-coated silica nanoparticles are uniformly mixed in a mass ratio of 100:3-5, the mixture is heated to 130-140°C and dried for 48-50 hours, and then the mixture is sent to a twin-screw high-speed composite spinning machine for spinning to obtain primary fibers. The primary fibers are stretched on a parallel stretching machine to obtain antistatic and antibacterial fibers.
3. The method for preparing an antistatic and antibacterial fiber according to claim 2, characterized in that: In step (3), the silica nanoparticles have a particle size of 300 nm, and the triethylamine-toluene mixed solution consists of triethylamine and toluene, wherein the volume ratio of triethylamine to toluene is 1:
1.
4. The method for preparing an antistatic and antibacterial fiber according to claim 2, characterized in that: The spinning process parameters of the twin-screw high-speed composite spinning machine for spinning in step (4) are as follows: the spinneret specification is 0.3mm*36f, the spinneret hole aspect ratio is 1:2, the spinning speed is 700m / min, the spinning temperature is 270°C, and the drawing process conditions are as follows: hot roller temperature is 65°C, setting temperature is 150°C, drawing speed is 300m / min, and drawing multiple is 3.2.
Citation Information
Patent Citations
Method for preparing polyester fibers with ultraviolet-resistant and anti-pilling composite function
CN102443877A
Preparation method of antimony-based polyester composite material
CN111040140A